Vulvar Lichen Sclerosus: Efficacy of Photodynamic Therapy Under Conscious Sedation with Inhaled 50% Nitrous Oxide and Oxygen Mixture - Cabete, J (2013)
Anogenital lichen sclerosus is a chronic, inflammatory, mucocutaneous disorder of significant morbidity. Common symptoms include pruritus, pain, dysuria, and dyspareunia, frequently of difficult control. Photodynamic therapy (PDT) may be an effective therapeutic option in selected cases refractory to first--‐line treatment options. However, procedure--‐related pain is a limiting factor in patient adherence to treatment. Conscious sedation and analgesia with a ready--‐to--‐use gas mixture of nitrous oxide and oxygen is useful in short--‐term procedures. It provides a rapid, effective, and short--‐lived effect, without the need for anesthesiology support. A 75--‐year--‐old woman presented with a highly symptomatic, histologically confirmed vulvar lichen sclerosus, with at least 15 years of evolution. Pain, pruritus, and dysuria were intense and disabling. Treatment with ultrapotent topical corticosteroids proved to be ineffective despite patient compliance. She was then referred for PDT. A total of 3 sessions were performed, held at a mean interval of 9 weeks, and under the analgesic and sedative effect of nitrous oxide/oxygen gas. Response to treatment was evaluated through a daily, self--‐reported pain rating scale. Dysuria remitted completely after the first PDT session. An 80% reduction in pruritus and pain was observed after the third session, and has been sustained for the past six months without further need for topical corticotherapy. Treatment sessions were well tolerated and pain-- free, with no side effects to report. PDT appears to be effective in the symptomatic treatment of vulvar lichen sclerosus. To the authors’ knowledge this is the first case reporting the use of inhaled nitrous oxide/oxygen gas mixture during PDT performed in the genital area. Its analgesic and sedative effects may increase patients’ adherence to this painful procedure. Furthermore, given its safety, it can be easily managed in outpatient clinics by trained dermatologists.